2021
DOI: 10.3390/ijms22062915
|View full text |Cite
|
Sign up to set email alerts
|

A New Anti-Estrogen Discovery Platform Identifies FDA-Approved Imidazole Anti-Fungal Drugs as Bioactive Compounds against ERα Expressing Breast Cancer Cells

Abstract: 17β-estradiol (E2) exerts its physiological effects through the estrogen receptor α (i.e., ERα). The E2:ERα signaling allows the regulation of cell proliferation. Indeed, E2 sustains the progression of ERα positive (ERα+) breast cancers (BCs). The presence of ERα at the BC diagnosis drives their therapeutic treatment with the endocrine therapy (ET), which restrains BC progression. Nonetheless, many patients develop metastatic BCs (MBC) for which a treatment is not available. Consequently, the actual challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Finally, we studied the anti-proliferative effects of CHK1 inhibitors ( i.e., AZD, Prexa, MK) in MCF-7 and Y537S tumor cell spheroids [ 7 , 9 ] as well as in alginate-based cultures [ 22 , 23 ] to understand if differences in the effect of these drugs exist in cells grown in 3D structures [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we studied the anti-proliferative effects of CHK1 inhibitors ( i.e., AZD, Prexa, MK) in MCF-7 and Y537S tumor cell spheroids [ 7 , 9 ] as well as in alginate-based cultures [ 22 , 23 ] to understand if differences in the effect of these drugs exist in cells grown in 3D structures [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tumor spheroid formation was performed as previously reported [ 7 , 9 ]. Briefly, MCF-7 and Y537S cells were seeded (10,000 cells/well) in ultra-low attachment surface 24-well-plates (Sigma-Aldrich) with 1 ml/well in growing condition for 24 h. Next, using an optical microscope, pictures had been taken for each well in untreated conditions ( i.e., time 0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cells are the best choice to include in the drug-delivery system and models. Manuela Cipolletti et al [ 18 ] exploited a novel anti-estrogen discovery platform using primary breast cancer cells to identify new Food and Drug Administration (FDA)-approved drugs inhibiting E2:ER signaling to cell proliferation. Yongli Chen et al [ 19 ] developed a microwell array microfluidic system to form diverse spheroids of breast cancer cell T47D and other human cancer cell lines of HepG2 and HCT116 for drug susceptibility testing and offline drug signaling pathways.…”
Section: Various In Vitro Breast Models On a Microfluidic Chipmentioning
confidence: 99%
“…In particular, the readers of this Special Issue will learn about the anti-tumor activity of neosynthesized, natural, and already-available drugs that could be used as new anti-BC drugs. Indeed, the contributing authors have reported the antiproliferative activity of berberine and troglitazone derivatives, resveratrol analogs, atoquavone, clotrimazole, fenticonazole, compounds specifically targeting mitochondrial activity, and valproic acid, as well as NAMPT and carbonic anhydrase IX inhibitors [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
mentioning
confidence: 99%